Enhancing Character Education in the New Normal Era through Academic Guidance and Outdoor Learning Methods in Malanggaten Village - Anisa Nur Azizah; Putri Febiyani; Tria Mardiana; Tri Amalia (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research addresses the educational implications of the Covid-19 pandemic, specifically the shift to remote learning. The study focuses on a community initiative providing home-based academic support to elementary students in Malanggaten Village. The significance of this research lies in understanding the challenges parents face in facilitating remote education. Method: Employing mixed methods, the research utilises surveys and interviews to explore students' and parents' challenges. Thematic coding and statistical analysis are applied for data interpretation. Practical Applications: The study offers educators, parents, and policymakers valuable insights into remote education. It suggests effective strategies for home-based learning and enhancing parental involvement, thereby improving students' academic performance. Conclusion: This research underscores the importance of community-driven initiatives, like home-based academic support, in addressing the challenges of remote education. It emphasises collaborative approaches among schools, parents, and communities for sustained and effective learning. This study contributes practical strategies for navigating educational challenges under unprecedented circumstances.